Uncertainty shocks and firm dynamics: Search and monitoring in the credit market - Thomas Brand; Marlène Isoré; Fabien Tripier (Bank of Finland, 2017)
We develop a business cycle model with gross flows of firm creation and destruction.The credit market is characterized by two frictions. First,entrepreneurs undergo a costly search for intermediate funding to create a firm. Second, upon a match, a costlystate-verification contract is set up. When defaults occurs, banks monitor firms, seize their assets, and a fraction of financial relationships are severed. The model is estimated using Bayesian methods for the U.S. economy. Among other shocks, uncertainty in productivity turns out to be a major contributor to both macro-financial aggregates and firm dynamics.
URN:NBN:fi:bof-201711231670
Keywords: D8; E3; E4; E5; 330